2011
DOI: 10.1111/j.1526-4610.2011.01994.x
|View full text |Cite
|
Sign up to set email alerts
|

Scuba Diving Is Not Associated With High Prevalence of Headache: A Cross‐Sectional Study in Men

Abstract: Scuba diving, an intense physical activity characterized by cerebral micro-vascular distress, is not associated with cephalalgia, as a whole, or migraine, tension headache or migraine with aura, more commonly than in a matched, non-diving, population. A longitudinal study may disclose if diving may act as a protective factor in the occurrence of crises of cephalalgia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…A study of NCAA athletes found that 23% of athletes reported a history of migraine (5), a higher prevalence than what has been reported in the general population, although likely more similar when prevalence is adjusted for age, as migraines are typically seen in younger adults. Given that cross-sectional studies have not detected a difference in migraine prevalence between scuba divers and the general population (6), we suggest that there is likely no difference in migraine prevalence between the general population and the underwater aquatic athlete. Additional research is needed, as there is a lack of migraine prevalence data in the other aquatic athlete categories.…”
Section: Common Headaches In the General Populationmentioning
confidence: 70%
See 2 more Smart Citations
“…A study of NCAA athletes found that 23% of athletes reported a history of migraine (5), a higher prevalence than what has been reported in the general population, although likely more similar when prevalence is adjusted for age, as migraines are typically seen in younger adults. Given that cross-sectional studies have not detected a difference in migraine prevalence between scuba divers and the general population (6), we suggest that there is likely no difference in migraine prevalence between the general population and the underwater aquatic athlete. Additional research is needed, as there is a lack of migraine prevalence data in the other aquatic athlete categories.…”
Section: Common Headaches In the General Populationmentioning
confidence: 70%
“…TTHs are common within the general athletic population with an incidence of 12.3% within National Collegiate Athletic Association (NCAA) athletes (5). Rates of TTH do not seem to be higher in the aquatic athlete (6). Only a small subset of patients reach out for medical treatment for tension headaches, as over-the-counter (OTC) medications are normally sufficient to treat a TTH.…”
Section: Tension-type Headachesmentioning
confidence: 99%
See 1 more Smart Citation